Handbook of research on resource management and the struggle for water sustainability in Africa - Netshiozwi, Edzisani; Bazaanah, Prosper; Mtapuri, Oliver; Nojiyeza, Innocent (IGI Global, 2021)
The Handbook of Research on Resource Management and the Struggle for Water Sustainability in Africa presents practical examples of integrated water resources management (IWRM) implementation in African countries. It further addresses the contemporary issues of alternative energy as part of climate change mitigation and utilizes case studies to examine how communities adapt to climate change. Covering topics such as climate justice, ecological governance, and political ecology, this major reference work is a dynamic resource for government officials, sociologists, climate scientists, activists, students and educators of higher education, academicians, and researchers in the fields of social sciences, government, developmental studies, international relations, and political science